Interactions of protamine with the marine bacterium, Pseudoalteromonas sp. NCIMB 2021. (1st March 2014) - Pustam, A.; Smith, C.; Deering, C.; Grosicki, K.M.T.; Leng, T.Y.; Lin, S.; Yang, J.; Pink, D.; Gill, T.; Graham, L.; Derksen, D.; Bishop, C.; et al.
Abstract: Pseudoalteromonas sp. NCIMB 2021 (NCIMB 2021) was grown in synthetic seawater (SSW) containing pyruvate, in the presence (SSW ++ ) and absence (SSW – ) of divalent cations. Cultures contained single cells. Addition of the cationic antibacterial peptide (CAP), protamine, did not inhibit, but rather increased, the growth of NCIMB 2021 in SSW ++ and caused the bacteria to grow in chains. Bacterial growth was assessed using turbidity, cell counts and the sodium salt of resazurin. In SSW −, NCIMB 2021 was no longer resistant to protamine. The minimum inhibitory concentration (MIC) was 5 mg ml −1 . Significance and Impact of the Study: Protamine is a cationic antimicrobial peptide (CAP), which is active against a variety of bacteria. This is the first in‐depth study of the interaction of protamine with a marine bacterium, Pseudoalteromonas sp. NCIMB 2021. Our results show that protamine is only active in seawater in the absence of divalent cations. In the presence of the divalent cations, Mg 2+ and Ca 2+, protamine enhances the growth of Pseudoalteromonas sp. NCIMB 2021 and produces chains rather than individual cells. These are important considerations when deciding on applications for protamine and in terms of understanding its mechanism of action.